FOOD AND FEEDING OF THE MUD CRAB SCYLLA SERRATA FORSKAL (DECAPODA : PORTUNIDAE) FROM KARWAR WATERS - Prasad, P N; Neelakantan, B (Indian Journal of Fisheries, 2011)
The food habits of the mud crab, Scylla serrata from Karwar waters were studied. A total of 151 crabs over a range of 41.04-136.82 mm (carapace width) representing ten size groups were examined. The principal dietary constituents, based on occurrence were crustaceans, detritus, molluscs, fish and miscellaneous items. Based on volumetric measurements - detritus, fish and crustaceans were the major trophic components comprising 35.70%, 23.57% and 18.37% of the total food volume respectively. Detritus was the major food group in juvenile crabs (<70mm) while in sub-adults (81-110 mm) and adult (< 110 mm) specimens it was the remains of crustaceans and fish.